Coagulation failure is associated with bleeding events and clinical outcome during systemic inflammatory response and sepsis in acute‐on‐chronic liver failure: An observational cohort study. (7th February 2019) - Premkumar, Madhumita; Saxena, Priyanka; Rangegowda, Devaraja; Baweja, Sukriti; Mirza, Roshni; Jain, Priyanka; Bhatia, Puja; Kumar, Guresh; Bihari, Chhagan; Kalal, Chetan; Vyas, Tanmay; Choudhury, Ashok; et al.
Abstract: Background: Patients with acute‐on‐chronic liver failure (ACLF) have coagulation failure in the setting of systemic inflammatory syndrome (SIRS), sepsis and extra‐hepatic organ failures. Methods: Consecutive ACLF patients without sepsis at baseline were assessed at days 0, 3 and 7 with thromboelastography (TEG) and specific assays (Factor VIII, von Willebrand factor [vWF], protein C and antithrombin III [ATIII]) and followed for development of sepsis, bleeding and outcome. Results: Of 243 patients, 114 (63% ethanol related; mean age 44.3 ± 11.7 years; 90% male) were recruited. SIRS was noted in 39 (34.2%), 45 (39.5%) and 46 (40%) patients at days 0, 3 and 7 and sepsis in 28 (24%) and 52 (56.1%) patients at days 3 and 7 respectively. The 28‐ and 90‐day survivals were 62% and 51% respectively. A hypocoagulable TEG at baseline was a predictor of bleeding (hazard ratio [HR] 2.1; CI 1.6‐4.9; P = 0.050) and mortality (HR 1.9; CI 1.3‐7.9; P = 0.043). ACLF patients had increased Factor VIII, vWF, tissue factor levels and tissue plasminogen activator (tPA) activity with reduced protein C and ATIII. Coagulation parameters like Coagulation Index (HR 2.1; CI 1.1‐4.5; P = 0.044), clot lysis (HR 3.2; CI 1.9‐3.4; P = 0.033), low protein C < 30% (HR 2.1; CI 1.5‐2.8; P = 0.017), ATIII (HR 1.4; CI 1.7‐3.1; P = 0.052) and tPA (HR 1.5; CI 1.1‐2.4; P = 0.052) were predictors of mortality at day 28. Protein C activity <30% (HR 1.3; CI 1.0‐2.9; P = 0.042) and tPA >20 ng/mL (HR 1.2; CI 1.1‐2.1; P = 0.040) predicted mortality when adjusted for age, gender and baseline MELD. Conclusions: Dynamic coagulation derangements, measured by TEG, determine the likelihood of bleeding and mortality in ACLF.